Bone density decreased in asthmatic children treated by inhaled budesonide - (:unkn) unknown (My University, 1997)
Increased use and earlier introduction of inhaled corticosteroids in the long-term management of asthma raises concerns about the side-effects of these medications in children. There is no published data on the effect of longterm inhaled budesonide therapy on bone density in asthmatic children. In a cross-sectional study, we compared bone density of 13 children (3-13.5 years of age) with moderate to moderately-severe asthma receiving inhaled budesonide at a daily dose of 400-800 ng/day for 7-45 months (Group I), with age- and sex-matched 11 mild asthmatic controls (Group II). L1-L4 spine density was measured by dual-energy-x-ray absorptiometry (DEXA). Data were converted to z scores and compared between the two groups. Height measurements were converted to z scores and baseline values were compared with the values obtained during the last visit in each group. Bone density of patients in Group I was found significantly lower than that of the Group II (Mann-Whitney U test, p=0.04). Multiple regression analysis did not reveal any significant correlation between bone density (dependent variable) and either cumulative budesonide dose (regression coefficient=0.003, p=0.3) or the duration of treatment (regression coefficient=0.07, p=0.28) in group I. Height Z scores did not change significantly in either group during the study. Bone density may be affected in asthmatic children due to long-term treatment with inhaled budesonide. The findings remains to be confirmed with longitudinal Studies ©1997 Wiley-Liss, Inc.